Extensive inflammatory cell infiltration in human skeletal muscle in response to an ultraendurance exercise bout in experienced athletes - Marklund, P.; Mattsson, C. M.; Wahlin-Larsson, B.; Ponsot, E.; Lindvall, B.; Lindvall, L.; Ekblom, B.; Fadi, F. (Journal of Applied Physiology, 2013)
The impact of a 24-h ultraendurance exercise bout on systemic and local muscle inflammatory reactions was investigated in nine experienced athletes. Blood and muscle biopsies were collected before (Pre), immediately after the exercise bout (Post), and after 28 h of recovery (Post28). Circulating blood levels of leukocytes, creatine kinase (CK), C-reactive protein (CRP), and selected inflammatory cytokines were assessed together with the evaluation of the occurrence of inflammatory cells (CD3+, CD8+, CD68+) and the expression of major histocompatibility complex class I (MHC class I) in skeletal muscle. An extensive inflammatory cell infiltration occurred in all athletes, and the number of CD3+, CD8+, and CD68+ cells were two- to threefold higher at Post28 compared with Pre (P < 0.05). The inflammatory cell infiltration was associated with a significant increase in the expression of MHC class I in muscle fibers. There was a significant increase in blood leukocyte count, IL-6, IL-8, CRP, and CK at Post. At Post28, total leukocytes, IL-6, and CK had declined, whereas IL-8 and CRP continued to increase. Increases in IL-1ß and TNF-a were not significant. There were no significant associations between the magnitude of the systemic and local muscle inflammatory reactions. Signs of muscle degenerative and regenerative events were observed in all athletes with various degrees of severity and were not affected by the 24-h ultraendurance exercise bout. In conclusion, a low-intensity but very prolonged single-endurance exercise bout can generate a strong inflammatory cell infiltration in skeletal muscle of well-trained experienced ultraendurance athletes, and the amplitude of the local reaction is not proportional to the systemic inflammatory response.